HUBUNGAN MUTU PELAYANAN KESEHATAN TERHADAP MINAT KUNJUNGAN ULANG PASIEN RAWAT JALAN DI PUSKESMAS PAKUAN BARU KOTA JAMBI - Nurul Safana Rizki; Erna Elfrida Simanjuntak; Anvika Adha Taufik (Journal of Hospital Administration and Management (JHAM), 2026)
Healthcare service quality is a key factor influencing patient satisfaction and their decision to revisit healthcare facilities. Fluctuations in outpatient revisit rates at the Pakuan Baru Community Health Center, Jambi City, indicate the need to evaluate the quality of healthcare services provided. This study aimed to analyze the relationship between healthcare service quality and outpatient revisit intention at the Pakuan Baru Community Health Center, Jambi City. A quantitative study with a correlational design was conducted involving 100 respondents selected through an incidental sampling technique. Data were collected using a structured questionnaire and analyzed using the Pearson Product Moment correlation test with a significance level of 5%. The results revealed a positive and statistically significant relationship between healthcare service quality and patients' revisit intention (r = 0.895; p < 0.001), indicating a very strong correlation. Analysis based on the SERVQUAL dimensions showed that all dimensions were significantly associated with revisit intention, with empathy (r = 0.893) and tangibles (r = 0.870) demonstrating the strongest correlations. These findings suggest that improving healthcare service quality, particularly in the dimensions of empathy, tangibles, assurance, reliability, and responsiveness, may enhance patients' intention to revisit healthcare services. Therefore, healthcare service quality plays a crucial role in fostering patient loyalty and promoting the sustainable utilization of healthcare services at the Pakuan Baru Community Health Center, Jambi City.